Tax loss carryforward disclosure - Vanessa Flagmeier; Jens Müller (Schmalenbach Journal of Business Research (SBUR), 2024)
This study examines firms' voluntary disclosure of tax loss carryforward (TLCF) information. We measure the content and presentation of TLCF information by a~disclosure score based on hand collected data from annual reports. Our identification strategy employs new proprietary data to control for overall reporting quality. We argue and find that uncertainty about the usability of TLCF is a~key driver of voluntary TLCF disclosure. The disclosure score is on average 3.86 points higher for firms with a~strong loss history vis-à-vis firms without such a~loss history. This positive association is economically meaningful, since the sample mean for the disclosure score is 8.88 (median 7.5). We also find that the content and type of disclosure vary systematically with the signal of uncertainty. In instances of historic uncertainty, firms exhibit increased reporting on the reasons and mechanisms behind changes in TLCF. Conversely, in the case of future uncertainty, they increase disclosure related to valuation allowance information. Our study provides detailed and unique insights into TLCF disclosure, suggesting that managers enrich the information environment with voluntary disclosure that caters to expected investors' needs.
Keywords: M41; M48; 650; Deferred taxes; Disclosure; Tax footnote; Tax loss carryforwards; Uncertainty